Frommer's easyguide to Disney World, Universal and Orlando 2017 - Cochran, Jason ([New York, New York] : Frommer Media LLC, 2017)
Provides a concise guide to the Orlando area, Universal Studios, and Walt Disney World with information about accommodations, restaurants, shopping, walking tours, and nightlife.
Includes indexes.
Keywords: Amusement parks -- Florida -- Orlando -- Guidebooks; Amusement parks -- Orlando (Fla.).; Walt Disney World (Fla.) -- Guidebooks; Universal Studios Florida (Orlando, Fla. : Amusement park) -- Guidebooks; Orlando Region (Fla.) -- Guidebooks; Walt Disney World (Fla.) -- Guidebooks; Universal Studios Florida (Orlando, Fla. : Amusement park) -- Guidebooks; Orlando Region (Fla.) -- Guidebooks; Travel guides